Avaliação de sistemas fotovoltaicos como proteção solar e fachada ventilada em relação à eficiência energética do edifício - Santos, Maurício Picetti dos (2021)
In Brazil, the national energy system is predominantly composed of renewable sources, allowing to obtain energy through cyclical resources such as water source, which corresponds to the main energy source in the country. This, however, is characterized by centralized generation and distant from consumption units, causing energy losses in transmission, and significant environmental impact due to the installation of hydroelectric plants, such as the relocation of communities and disfigurement of the local ecosystem. Faced with the need to diversify energy sources, photovoltaic solar energy is an alternative to promote energy generation from a renewable source and to bring generation centers closer to consumer units, reducing losses during energy transport. Also, based on the ability to compose modular structures, photovoltaic systems can be integrated into the building envelope as passive components, favoring energy efficiency. In this context, the research evaluated the influence of photovoltaic sets in the form of shading devices and ventilated facades in promoting energy efficiency when applied to the north and west envelopes of standard buildings at the Federal University of Santa Maria on the Camobi campus. A virtual model of the buildings was developed where the photovoltaic sets were inserted to obstruct the incidence of excessive solar radiation and potential for energy generation; in addition, the sets were reproduced in the roof of the model, in order to constitute reference sets. Then, simulations were performed using PVsyst software, to analyze the electrical generation of the sets, and DesignBuilder, to evaluate the variation in consumption in the model. Through the energy balance, it was verified that the photovoltaic sets contributed to the energy efficiency of the virtual model, although the sets positioned on the roof had better performance due to the potential in electrical generation. The ventilated facade and the shading devices developed reductions in consumption through artificial cooling, but increased consumption in lighting, while energy generation was conditioned to losses due to shading and the angle of incidence of radiation on the modules. In the evaluations, only the photovoltaic integrated shading devices for the north orientation promoted reductions in the annual electrical consumption (decrease of 3.39%), while, in the other configurations, they promoted an increase in electrical consumption. In both orientations, the positive energy balance was verified with the modules of the ventilated facade on the roof (Cob. Fachada Ventilada), with a positive energy balance of 108.28 MWh for the west orientation and 134.47 MWh for the north. The research explored the use of building envelopes for electricity generation through photovoltaic systems, as well as their application in the form of passive solutions to reduce energy demand. Therefore, considering the potential of photovoltaic technology, the study allows for new understandings for the application of these systems to promote energy efficiency in buildings.